Economic and Social Rehabilitation Management Law Affected by the Coronavirus Disease 2019(COVID-19) Outbreak Under the Sustainable Development Principles in Thailand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Research shows that the coronavirus epidemic has resulted in a sudden disappearance of income from tourism and exports, the country's main source of income. Small entrepreneurs lack capital and people lack purchasing power. Thailand has to manage economic and social recovery under the principles of sustainable development, revert to strengthening the country in line with national strategy, and building a solid foundation by turning the COVID-19 crisis into an opportunity building the local and community-based economy while spreading prosperity to the region in the new economic corridors. Infrastructure upgrades and related production processes, economic and social recovery plans from the impact of COVID-19, should be upgraded under Emergency Decree Authorising the Ministry of Finance to Raise Loans to Solve Problems, to Remedy And Restore the Economy And Society as Affected by the Coronavirus Disease Pandemic, B.E. 2563 (2020). It aims to meet the key goals of strengthening the foundation economy by focusing on employment, new theory agriculture, community tourism, village funds, and logistics. Emphasize diversification into the region by investing in potential new economic corridors (Nec, NeEC, CWEC, SEC) to support future sustainable growth.